Prevalence and antimicrobial resistance patterns of Enterococcus species isolated from laying hens in Lusaka and Copperbelt provinces of Zambia: a call for AMR surveillance in the poultry sector. Issue 6 (21st December 2022) - Mudenda, Steward; Matafwali, Scott Kaba; Malama, Sydney; Munyeme, Musso; Yamba, Kaunda; Katemangwe, Patrick; Siluchali, Godfrey; Mainda, Geoffrey; Mukuma, Mercy; Bumbangi, Flavien Nsoni; Mirisho, Robert; Muma, John Bwalya
Abstract: Background: The use of antimicrobials in layer poultry production for improved production, growth promotion, prophylaxis and treatment purposes has contributed to the development of antimicrobial resistance (AMR) in poultry. In Zambia, there is a paucity of information on the prevalence and AMR patterns of Enterococcus species isolated from laying hens. Objectives: This study investigated the prevalence and AMR patterns of enterococci isolated in layer hens in Lusaka and Copperbelt provinces of Zambia. Methods: A cross-sectional study was conducted from September 2020 to April 2021. Three hundred and sixty-five pooled cloacal swab samples were collected from 77 layer poultry farms. Enterococci identification and confirmation were performed using Analytical Profile Index (API 20 STREP) and 16S rRNA sequencing, respectively. A panel of nine antibiotics was used for antibiotic susceptibility testing and interpreted according to the CLSI 2020 guidelines. Data were analysed using SPSS version 23 and WHONET 2020. Results: A total of 308 (83%) single Enterococcus species isolates were obtained and showed resistance to tetracycline (80.5%), erythromycin (53.6%), quinupristin/dalfopristin (53.2%), ampicillin (36.72%), vancomycin (32.8%), linezolid (30.2%), ciprofloxacin (11.0%), nitrofurantoin (6.5%) and chloramphenicol (3.9%). The prevalence of enterococci resistant to at least one antibiotic was 99.4% ( n = 306), of which 86% ( n = 265) were MDR. Conclusions: This study found a high prevalence of antimicrobial-resistant enterococci. The presence of MDR requires urgent intervention and implementation of AMR surveillance strategies and antimicrobial stewardship programmes in layer poultry production in Zambia.